Promoting Distance Learners’ Cognitive Engagement and Learning Outcomes: Design-Based Research in the Costa Rican National University of Distance Education - Joo, K. P.; Andrés, Carmen; Shearer, Rick (International Review of Research in Open and Distributed Learning, 2014)
To explore effective learning design for students’ cognitive engagement, a design-based case study was conducted in a quality control course in the Costa Rican National University of Distance Education between the 2011 and 2012 academic years. The course was revised for the 2012 provision in terms of the assignment structure, the number of face-to-face sessions, and facilitation strategies. This study documents how the course redesign impacted the distance learners’ cognitive engagement and learning outcomes. Theories of cognitive engagement and transactional distance informed the design-based investigation. Research findings indicate that the design revisions positively influenced both students’ cognitive engagement and learning outcomes within this distance higher education context; however, the student performance represented by their assessment grades might not always reflect this improvement.